AI-ENABLED STRATEGIC LEADERSHIP AND HUMAN INSIGHT - Halima Idris (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This article examines strategic leadership in the age of artificial intelligence by emphasizing the need to balance machine intelligence with human insight. Drawing from Halima Idris's conference material and supported by contemporary literature on digital leadership, AI governance, ethics, and organizational transformation, the article argues that AI strengthens leadership through evidence-based decision-making, forecasting, fraud detection, educational innovation, healthcare support, and improved governance. However, AI cannot replace human qualities such as ethical judgment, empathy, accountability, cultural understanding, integrity, and wisdom. The study employs a conceptual literature-based method to synthesize key ideas on AI-enabled leadership and responsible decision-making. The discussion shows that effective leaders should use AI as a decision-support instrument while retaining responsibility for final decisions and social consequences. The article recommends that governments develop responsible AI policies, universities integrate AI literacy with ethics and critical thinking, and organizations build transparent AI practices while reskilling their workforce. The article concludes that sustainable development in the AI era requires hybrid leaders who combine technological competence with human values.